PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2016) - Intan Isnaeni, 14.05.52.0096; Hardiningsih, Pancawati (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effect of profitability, capital structure and managerial ownership on firm value.This type of research uses empirical studies. This research was carried out using documentation method using data from the Indonesia Capital Market Directory (ICMD) and the financial statements of manufacturing companies. Samples were taken using purposive sampling technique. The sample consisted of 143 observations from 466 manufacturing companies listed on the Indonesia Stock Exchange in 2014-2016. The data analysis technique used is Multiple Regression Analysis.The results showed that the profitability variable had a significant effect on firm value, capital structure variables had a significant effect on firm value, while managerial ownership had no effect on firm value. Keywords: Profitability, Capital Structure, Managerial Ownership, and Company Value